Bindeelementer i danske nominalkomposita - Szubert, Andrzej (Wydawnictwo Naukowe UAM, 2009)
Formålet med artiklen er præsentere bindeelementer i danske nominalkomposita. Artiklen præsenterer eksisterende bindeelementer i danske nominale komposita og forsøger at vise mekanismerne, som står bag valget af bindeelement. Artiklen forsøger at afklare om man har at gøre med bindeelementer eller flektion i et nominalkompositum. Som en del af konklusionen er der vist lidt statistik i forbindelse med bindeelementer i danske nominale komposita.

The aim of the article is to present the phenomenon of linking elements in Danish nominal compounds. The article presents the possible linking elements being used in Danish nominal compounds and tries to show the mechanisms in the choice of a particular linking element. There is also a discussion, whether we have to do with linking elements or inflexion in Danish nominal compounds. As a part of the conclusion some statistics on the linking elements in Danish nominal compounds is shown.
Linking Elements in Danish Nominal Compounds
Keywords: bindeelement; nominalt kompositum; fugeelement; linking element; nominal compound